2021
DOI: 10.1016/j.jcot.2021.05.011
|View full text |Cite|
|
Sign up to set email alerts
|

Superior capsular reconstruction for irreparable rotator cuff tears: A literature review and specialist practice report

Abstract: Background: Recent evidence continues to confirm the effectiveness of arthroscopic superior capsular reconstruction (SCR) in relieving pain and improving function in an irreparable cuff deficient shoulder. This paper presents an up-to-date literature review on SCRand a tertiary referral unit experience in the United Kingdom. Methods: Data was prospectively collected on patients undergoing SCR for irreparable rotator cuff tears using a dermal allograft. Patients with already established arthritis were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[36] From a biomechanical point of view, when the shoulder joint is elevated, the graft can play a role in strengthening the stable arm bone and soft tissue, allowing the entire front and rear of the shoulder joint to pass through. [37] Early clinical results of the application of autologous fascia lata are expected to reduce pain and function in patients. [38] Another study by Mihata et al [39] in 2018 showed that the reversal rate of pseudoparalysis in patients with IRCTs was 94.9% with SCR, which was comparable to the 90% pseudoparalysis in SCR patients reported by Denard et al [40] pseudoparalysis (no more than 45 in forward flexion) was reversed with consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…[36] From a biomechanical point of view, when the shoulder joint is elevated, the graft can play a role in strengthening the stable arm bone and soft tissue, allowing the entire front and rear of the shoulder joint to pass through. [37] Early clinical results of the application of autologous fascia lata are expected to reduce pain and function in patients. [38] Another study by Mihata et al [39] in 2018 showed that the reversal rate of pseudoparalysis in patients with IRCTs was 94.9% with SCR, which was comparable to the 90% pseudoparalysis in SCR patients reported by Denard et al [40] pseudoparalysis (no more than 45 in forward flexion) was reversed with consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Other alternative procedures for irreparable posterosuperior RCTs include debridement, biceps tenotomy or tenodesis, subacromial decompression, tendon transfer, and bridging graft ( 30 ).…”
Section: Indicationsmentioning
confidence: 99%
“…c o m / l o c a t e / j c o t significant interest in using bridging graft connecting the superior surface of the glenoid to greater tuberosity footprint to restore the superior capsule of the shoulder. 12 Insertion of a biodegradable balloon in the subacromial space to reduce acromio-humeral contact and aid deltoid function has also been explored. 13 Such "disruptive" technologies seek to lower the surgical risks and morbidities associated with tendon transfers which require a more extensive surgical dissection.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%